3D discrete wavelet transform‐based feature extraction for hyperspectral face recognition. Issue 1 (9th November 2017) - Ghasemzadeh, Aman; Demirel, Hasan
Abstract : Facial hyperspectral image analysis has become a popular topic since it provides additional spectral information on subjects unlike the 2D face imagery which only has spatial information, hence it has an opportunity to improve face recognition accuracy. Three new methods for feature extraction for facial hyperspectral image classification are proposed. The methods employ a three‐dimensional discrete wavelet transform (3D‐DWT) to extract features from facial hyperspectral images. One of the advantages of 3D‐DWT for feature extraction in hyperspectral images is that the horizontal, vertical and spectral information are processed in parallel. The most important characteristic of 3D‐DWT is decomposing hyperspectral images into a set of spatio‐spectral frequency subbands. The study proposes three methods using 3D‐DWT for feature extraction: 3D‐subband energy, 3D‐subband overlapping cube and 3D‐global energy. The k‐NN and collaborative representation‐based classifier (CRC) are used to process extracted feature vector datasets, where classification accuracies are evaluated by four test scenarios. The results under different test scenarios revealed that accuracy of proposed 3D‐DWT methods is superior to alternative methods using spatio‐spectral classification.